Pengaruh Profitabilitas, Leverage, Free Cash Flow terhadap Manajemen Laba: Peran Moderasi Pertumbuhan Penjualan - Wiratri Anindya Bella; Nindya Rieska Shafira; Talitha Mukti Deviani; Sudradjat Sudradjat (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to examine the effect of profitability, leverage, and free cash flow on earnings management with sales growth as a moderating variable in energy sector companies listed on the Indonesia Stock Exchange during 2021–2024. The data used in this study is secondary financial statement data, which was analyzed using a quantitative approach and selected through purposive sampling, resulting in a sample of 65 companies. The analysis was conducted using multiple linear regression with EViews 12 software. Based on the test results, free cash flow was found to have a positive and significant effect on earnings management, while profitability and leverage had no significant effect. Sales growth strengthens the influence of profitability on earnings management, weakens the influence of free cash flow, and does not moderate the leverage relationship. This study contributes to strengthening agency theory and positive accounting theory regarding opportunistic manager behavior, and provides practical benefits for management, investors, and regulators in assessing the quality of financial reports in the energy sector. Future research is expected to include aspects of corporate governance and macroeconomic factors in order to provide a more comprehensive understanding of the factors that determine earnings management.